An assessment of the impact of Private equity funding on agricultural development in Namibia - Shimbamba, Werner (Graduate School of Business (GSB), 2024)
This study was an assessment of the impact that Private equity funding has on agricultural development in Namibia. The study's research questions were: how has private equity funding resulted in agricultural development in Namibia? Also, what strategies have been implemented to attract private equity funding to boost agricultural development? The study adopted a qualitative research approach to map up ways to collect data. The sample of the study comprised of 25 farmers, private equity firms as well as banks and the sampling technique used to select these was purposive sampling. Data collection was performed using a semi-structured interview guide through interviews with key informants. Thematic analyse was used as the data analysis method for this study. It was established from the study that private equity funding has not played a significant role in the development of the Namibian agricultural sector with most farmers especially small scale still struggling to acquire alternate capital injections to expand and modernise their operations. It was further established that the most prevalent sources of financing were through state-owned institutions such as Agribank that usually give bailouts and subsidies to farmers in various areas to increase production of certain products that the government can then facilitate to import. Moreover, farmers get funding through loans from commercial banks which at have also been seen to at times suffocate farmers due to high interest rates. It was also found that there seems to be a lack of understanding of private equity funding and how to access it and that leads to failure to take advantage of the benefits that it comes with. This lack of understanding has been identified to be as a result of lack of exposure, most farmers especially small scale being illiterate and a lack of information sharing or educational initiatives to help farmers identify the various possible funding sources they may access to help grow their farms. Some of the strategies that have been highlighted to solve this issue include promotion and development of Private Equity Funds in Agriculture, establishment of a private public partnership in the venture capital industry and that they should harness resources and avail them for this purpose. Additionally, Agribank and the Development Bank of Namibia should vigorously undertake awareness campaigns and educate the investment community about the true value and risks found in the agricultural sector as this could improve investors' appetite for such investments.